Electrochemical Sensors Technology - Muzibur Rahman, Mohammed; Mohamed Asiri, Abdullah (IntechOpen, 2017)
This book Electrochemical Sensors Technology mostly reviews the modem methods and significant electrochemical and electroanalytical applications of chemical sensors and biosensors. Chapters of this book are invited and contributed from the experts throughout the world from prominent researchers and scientists in the field of sensors and in the field of electro- and biochemistry. Each chapter provides technical and methodological details beyond the level found in typical journal articles or reviews and explores the application of chemical sensors, environmental sensors, and biosensors to a significant problem in biomedical and environmental science, also providing a prospectus for the future. This book compiles with the expert knowledge of many specialists in the construction and use of chemical sensors and biosensors including chemical sensors, biological sensors, DNA sensors, immunosensors, gaseous sensors, ionic sensors, bioassay sensors, lab-on-chips, devices, portable sensors, microchips, nanosensors, implantable microsensors, and so on in the field of fundamental and applied electrochemistry. Highlights and importance are laid on real or practical problems, ranging from chemical application to biomedical monitoring, from in vitro to in vivo, and from single cell to animal to human measurement. This offers a unique opportunity of exchanging and combining the scientist or researcher in electrochemical sensors in largely chemistry, biological engineering, electronic engineering, and biomedical and physiological fields.